Influencers and Unproven Health Claims: Curbing Misleading Promotion in the United States and Canada - Marcon, Alessandro; Murdoch, Blake; Caulfield, Timothy (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
The rise of social media has enabled influencers to shape public health discourse and promote unproven health products and interventions. Here we examine practical and regulatory challenges and opportunities relating to influencer-driven health marketing in the United States and Canada. Despite existing legal prohibitions on misleading advertising linked directly to influencers by official regulatory guidance, enforcement remains inadequate. Current regulatory frameworks permit vague health claims. Moreover, oversight differs between licensed health professional influencers and layperson influencers. Social media platforms are complicit in and/or indifferent to the amplification of misinformation, as it drives engagement and furthers their profit motives. To address misleading influencer health marketing, both “hard” and “soft” strategies are considered, including international policy coordination and algorithmic solutions that reduce the visibility of misleading content. One key challenge remains how to engender the willing participation of powerful multinational corporations with political and lobbying influence. We raise the potential usefulness of carefully crafted automated enforcement mechanisms, including AI-driven content monitoring systems and automated notice-and-takedown procedures, while simultaneously advocating for a balanced approach that respects freedom of expression. Updated, scalable, and equitable regulations and enforcement mechanisms are needed to protect consumers, foster evidence-based health communication, and restore accountability in digital health marketing.